“Being without restriction”: contemporary sociological theory and the gender anti-binary - Richards, Ezra (My University, 2023)
Canada and the US have seen recent increases in transphobic attitudes and policies, under the guise of “parental rights” or adherence to tradition. Trans people are often painted as predators attempting to indoctrinate children into “gender ideology,” and any deviance from the cisgender, male-female binary are seen as inherently dangerous or inappropriate, misconstruing and preventing trans liberation. Using sociological theories from Maurice Merleau-Ponty, the Frankfurt School, and Judith Butler, I propose a path beyond this transphobic discourse: redefine gender devoid of any and all labels and categories. This anti-binary attitude puts the emphasis on embodied experience, such that gender is centred around personal joy and self-awareness rather than external, societal criteria. With this anti-binary in place, gender liberation will extend not only to trans individuals, but to all individuals facing pressure from the gender culture industry.
Presented on April 19, 2024 at Student Research Day held at MacEwan University in Edmonton, Alberta.
Keywords: gender labels; gender roles; queer identity